Racial Equity and U.S. Law (Mary Ann Liebert, 2023)
History and experience teach us that our Constitution and laws can be instruments of racial discrimination and oppression as well as tools for advancing freedom and equality. The substance of our laws matters, and there is much to be learned from innovative policies and legal strategies around the country. In addition to laws promoting health equity and racial justice at the state, tribal, and local levels, a new federal Executive Order has the potential to drive major positive change if fully and properly implemented. Just as important, however, is linking legal advocacy with dynamic social movements, shrewd communication strategies, and courageous civic leadership that insists on transformative change. In this article, I briefly recount the turbulent relationship between law and equity in our nation; discuss the elements that can lead to major progress through law; and recommend specific steps that different actors can take to move an equity and opportunity agenda forward.